Shattering the boundaries through self-efficacy : exploring the social media habits of South African previously disadvantaged entrepreneurs - Stevens, Julie (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.